2020
DOI: 10.1186/s13037-020-00248-4
|View full text |Cite
|
Sign up to set email alerts
|

The novel immunomodulatory biologic LMWF5A for pharmacological attenuation of the “cytokine storm” in COVID-19 patients: a hypothesis

Abstract: Background: A common complication of viral pulmonary infections, such as in the ongoing COVID-19 pandemic, is a phenomenon described as a "cytokine storm". While poorly defined, this hyperinflammatory response results in diffuse alveolar damage. The low molecular weight fraction of commercial human serum albumin (LMWF5A), a novel biologic in development for osteoarthritis, demonstrates beneficial in vitro immunomodulatory effects complimentary to addressing inflammation, thus, we hypothesize that LMWF5A could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 66 publications
(77 reference statements)
0
22
0
Order By: Relevance
“…Furthermore, we observed significant decreases in CD206 expression by immunofluorescence ( Figure 4D). M2 macrophages are responsible for pro-inflammatory and pro-fibrosis cytokines in the lung commonly known as the "cytokine storm" [22,23] To determine if RP-832c affects these cytokines, we performed RT-PCR on mRNA extracted from naïve, BLM only, and RP-832c treated lungs. Interestingly, we observed significant decreases in TNF-α, IL-10, IL-6, CXCL1, and CXCL2 ( Figure 4E).…”
Section: Rp-832c Peptide Reduces Cd206 Expression and Fibrosis Markermentioning
confidence: 99%
“…Furthermore, we observed significant decreases in CD206 expression by immunofluorescence ( Figure 4D). M2 macrophages are responsible for pro-inflammatory and pro-fibrosis cytokines in the lung commonly known as the "cytokine storm" [22,23] To determine if RP-832c affects these cytokines, we performed RT-PCR on mRNA extracted from naïve, BLM only, and RP-832c treated lungs. Interestingly, we observed significant decreases in TNF-α, IL-10, IL-6, CXCL1, and CXCL2 ( Figure 4E).…”
Section: Rp-832c Peptide Reduces Cd206 Expression and Fibrosis Markermentioning
confidence: 99%
“…The other day when this author was surfing you tube, one thing surprised her was that so many people including many professionals do not know how to wash hands. The right way to wash hands is as follows: First, you need to lather the hand up after test the water temperature [24,25]. Do not burn yourself.…”
Section: Other Precautionsmentioning
confidence: 99%
“…We have recently reviewed the effects of both PGE 2 and PGJ 2 (and its derivatives) in severe inflammatory disease and have argued that the pro-and anti-inflammatory effects of these prostaglandins are so complex that, for clinical use, it would be better to use compounds that stimulate the natural progression of PGE 2 synthesis followed by inhibition of its synthesis, and then appearance of the PGJ 2 and its derivatives, in order to mimic the body's natural sequence of events when severe inflammation arises [13]. KD and the newly described syndrome associated with COVID-19 are logical diseases to consider using this approach.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Furthermore, evidence suggests LMWF5A also promotes the production of mediators required for resolving inflammation and enhances the barrier function of endothelial cultures. A more detailed description of the nebulized form trial protocol and rationale was recently published [13]. Although a nebulized form of LMWF5A has been proposed to treat COVID-19 respiratory disease, it seems more likely that intravenous therapy, either alone or as a supplement to IVIG therapy would be a more reasonable approach for a trial in KD patients and the recently observed SARS-CoV-2 associated disease.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation